Dual‐Phase CsPbBr3–CsPb2Br5 Perovskite Thin Films via Vapor Deposition for High‐Performance Rigid and Flexible Photodetectors. Issue 7 (20th December 2017) - Tong, Guoqing; Li, Huan; Li, Danting; Zhu, Zhifeng; Xu, Enze; Li, Guopeng; Yu, Linwei; Xu, Jun; Jiang, Yang
Abstract: Inorganic perovskites with special semiconducting properties and structures have attracted great attention and are regarded as next generation candidates for optoelectronic devices. Herein, using a physical vapor deposition process with a controlled excess of PbBr2, dual‐phase all‐inorganic perovskite composite CsPbBr3 –CsPb2 Br5 thin films are prepared as light‐harvesting layers and incorporated in a photodetector (PD). The PD has a high responsivity and detectivity of 0.375 A W −1 and 10 11 Jones, respectively, and a fast response time (from 10% to 90% of the maximum photocurrent) of ≈280 µs/640 µs. The device also shows an excellent stability in air for more than 65 d without encapsulation. Tetragonal CsPb2 Br5 provides satisfactory passivation to reduce the recombination of the charge carriers, and with its lower free energy, it enhances the stability of the inorganic perovskite devices. Remarkably, the same inorganic perovskite photodetector is also highly flexible and exhibits an exceptional bending performance (>1000 cycles). These results highlight the great potential of dual‐phase inorganic perovskite films in the development of optoelectronic devices, especially for flexible device applications. Abstract : New inorganic perovskite films with dual‐phase CsPbBr3 –CsPb2 Br5 fabricated by a physical vapor deposition process enable rigid and flexible photodetectors, which exhibit faster response time, excellent flexibility, and stability in the air.